Structure and management of Aleppo pine forests - Ciancio O.; Iovino F.; Mendicino V.; Menguzzato G.; Nicolaci A.; Nocentini S. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
The authors analyze the most prevalent structural types in Aleppo pine (Pinus halepensis Mill.) forests on the Upper Ionian Coast in the Province of Cosenza in order to evaluate the evolutionary dynamics resulting from silvicultural treatments and the forest fires that plague this area. The structural types found in this area are: even-aged, often resulting from fires on vast areas; pure forest with multi-storeyed structure, deriving from fellings generically defined as selection cuttings; two storeyed forests, resulting from selection cutting or clear-cutting with seed trees; mixed stands with an under-storey comprising species typical of the Mediterranean maquis and the upper storey characterized by Aleppo pine. The results obtained reveal some aspects that are peculiar to these forests both with reference to the evolutionary dynamics as well as the relationships among fires, the structural type, and past management.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)